2013
DOI: 10.1042/bst20130004
|View full text |Cite
|
Sign up to set email alerts
|

Determining the topology of stable protein–DNA complexes

Abstract: Difference topology is an experimental technique that can be used to unveil the topological structure adopted by two or more DNA segments in a stable protein-DNA complex. Difference topology has also been used to detect intermediates in a reaction pathway and to investigate the role of DNA supercoiling. In the present article, we review difference topology as applied to the Mu transpososome. The tools discussed can be applied to any stable nucleoprotein complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…14 It provides the ultimate level of abstraction of many biological processes, such as the open or close of ion channels, the assembly or disassembly of virus capsids, the folding and unfolding of proteins, and the association or dissociation of ligands. 13,[15][16][17][18][19][20][21] However, conventional topology or homology is truly free of metrics or coordinates and thus retains too little geometric information to be practically useful. Persistent homology is a new branch of algebraic topology that embeds multiscale geometric information into topological invariants to achieve the interplay between geometry and topology.…”
Section: Introductionmentioning
confidence: 99%
“…14 It provides the ultimate level of abstraction of many biological processes, such as the open or close of ion channels, the assembly or disassembly of virus capsids, the folding and unfolding of proteins, and the association or dissociation of ligands. 13,[15][16][17][18][19][20][21] However, conventional topology or homology is truly free of metrics or coordinates and thus retains too little geometric information to be practically useful. Persistent homology is a new branch of algebraic topology that embeds multiscale geometric information into topological invariants to achieve the interplay between geometry and topology.…”
Section: Introductionmentioning
confidence: 99%
“…This example illustrates the importance of local topological changes in addition to global topology in DNA-enzyme interactions. Random cyclization of DNA, enhanced by entangled DNA conditions in tight spaces such as bacteriophage DNA in capsid or site-specific recombination processes, can also lead to the formation of knots in the DNA [reviewed in (Darcy and Vazquez 2013)].…”
Section: Dna Topologymentioning
confidence: 99%
“…Partly because of this ambiguity, relating enzyme-mediated changes in DNA topology to DNA geometry often requires some assumptions about the geometries of nucleoprotein intermediates in the enzymatic pathway. 11,12 These assumptions can be difficult to confirm independently through measurements in solution; moreover, atomic-resolution crystallographic structures are not always helpful in resolving structural ambiguities because of inherently limited information about conformational dynamics. Thus, nuances such as conformational changes in the context of a cellular environment may not be fully revealed.…”
Section: Introductionmentioning
confidence: 99%
“…A previous topological study of tyrosine recombinases, including Cre, revealed an excess of (+)-noded knotted recombinant DNA products over (-)-noded topologies 29. This excess implies the existence of a productive right-handed recombination intermediate; however, no available crystallographic structure for any of these recombinases with their DNA target12 sites shows significant right-handed chirality. The data presented here provide the first direct evidence for a right-handed recombination intermediate in solution and also support apparent asymmetries in the arrangement of recombination sites observed by…”
mentioning
confidence: 95%